Peran Keluarga dalam Mendidik Buah Hati Menurut Rasulullah - Fitri Chairunisa; Masykur H Mansyur; Neng Ulya (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
The family has a very big influence on the first and foremost environment to shape the child's personality (heart grains). Therefore, in the process of educating children (children) in the family environment, it is obligatory to have knowledge and various ways of educating children (grains of the heart), especially the method or way of educating that Rasulullah SAW gave as our role model, because to produce a generation of children who are pious will not be separated according to the foundation of Islam, namely the Qur'an and the Sunnah. The purpose of this research is to find out how to educate the children of Rasulullah SAW who can create a rabbinic Muslim generation. The type of research used in this study is to use library research or library research. Where this research is the researcher does not do many case studies of the field but with a study of literature approaches from various book sources or in other words qualitative research. The result of the application of education from the Prophet Muhammad is the application of education that is sourced or comes from Allah SWT and has values that are able to produce a pious Muslim generation, both personally and socially, and education from the Prophet Muhammad through several stages that must be met by parents or family. Therefore, to determine the success of parents or families in educating children in accordance with the development and differences in the character of children who are owned by the Prophet Muhammad is the best way to prepare and produce in terms of moral, spiritual, and social children to become people of faith and piety.